THE USE OF LANGUAGE EXPERIENCE APPROACH IN WRITING SKILL - Andika Krisna Mukti; Ch. Evy Tri W (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
The objectives of the research are : 1) to find out whether Language Experience Approach (LEA) can improve students‟ Writing Skill on Narrative Text; and 2) to find out the implementation of LEA in teaching and learning writing at the eighth grade students of SMP N 16 Surakarta in 2019/2020 Academic Year especially in class VIII D is. The research was conducted at SMP N 16 Surakarta. It was conducted from October, 22th 2019 until January, 23rd 2020. The subject of the research was the students of class VIII D. In implementing the teaching and learning process, the researcher divided the research into two cycles. There were 2 meetings in cycle 1 and cycle 2. All meetings ended by Post-Test. Every meeting consisted of 5 steps : observing, questioning, exploring, associating, and communicating. In collecting the data, the reseacher used Test and Non Test. Tests included Pre-Test and Post-Test. Non Test included observation, interview , data analysis and documentation. In analyzing the data, the researcher used quantitative data and qualitative data . The result of Cycle 1 showed that some students were still less on organizing idea, vocabulary,language in use, content, and mechanics. Therefore, Cycle 2 showed that the use of LEA for organizing idea, vocabulary,language in use,content, and mechanics could improve the students‟ Writing Skill. The students‟ mean score in pre-test was 44.85, post-test 1 was 60.29, and post-test 2 was 73.08. And the t-test of cycle 1 was 8.56, and the t-test of cycle 2 was 10.65. Based on the result of the data from pre test, post test 1 and post test 2, it could be concluded that “The use of LEA can improve students‟ Writing Skill on Narrative Text in SMP N 16 Surakarta in 2019/2020 Academic Year, especially in class VIII D. So, LEA is a good and fun learning strategy for teaching and learning process. Key word: Writing Skill, Language Experience Approach (LEA) , Classroom Action Research.